Advances in Nanomaterials for Injured Heart Repair - Guo, Jiacheng; Yang, Zhenzhen; Wang, Xu; Xu, Yanyan; Lu, Yongzheng; Qin, Zhen; Zhang, Li; Xu, Jing; Wang, Wei; Zhang, Jinying; Tang, Junnan (Frontiers in Bioengineering and Biotechnology, 2021)
Atherosclerotic cardiovascular disease (ASCVD) is one of the leading causes of mortality worldwide. Because of the limited regenerative capacity of adult myocardium to compensate for the loss of heart tissue after ischemic infarction, scientists have been exploring the possible mechanisms involved in the pathological process of ASCVD and searching for alternative means to regenerate infarcted cardiac tissue. Although numerous studies have pursued innovative solutions for reversing the pathological process of ASCVD and improving the effectiveness of delivering therapeutics, the translation of those advances into downstream clinical applications remains unsatisfactory because of poor safety and low efficacy. Recently, nanomaterials (NMs) have emerged as a promising new strategy to strengthen both the efficacy and safety of ASCVD therapy. Thus, a comprehensive review of NMs used in ASCVD treatment will be useful. This paper presents an overview of the pathophysiological mechanisms of ASCVD and the multifunctional mechanisms of NM-based therapy, including antioxidative, anti-inflammation and antiapoptosis mechanisms. The technological improvements of NM delivery are summarized and the clinical transformations concerning the use of NMs to treat ASCVD are examined. Finally, this paper discusses the challenges and future perspectives of NMs in cardiac regeneration to provide insightful information for health professionals on the latest advancements in nanotechnologies for ASCVD treatment.